Duality between E-commerce and Cybersecurity: Case of Central Africa - (:unkn) unknown (My University, 2023)
In this article, the duality between e-commerce and cybersecurity in Central Africa’s case has been presented. To achieve this, a field study was conducted by submitting a question in order to make sure that the impact of cybersecurity on e-commerce in Africa in general and Central Africa in particular is real. A questionnaire was submitted to small and medium-sized business online sales companies, Congolese campuses, research laboratories, those who submit the articles online, and African Internet users. Risk assessments based on loopholes, threats, and countermeasures were also conducted. The results of this study are successful insofar as the results of the survey sufficiently prove the existence of the problem. The outcome of the risk assessment based on flaws, threats, and countermeasures is the panacea for the investigation, in the sense that strengthening countermeasures at the level of online merchants minimizes the risk of being attacked or victimized.
Keywords: African Research